An Approach to the Development of a Distance Education Module - Thusbara E. I. Fernando; Rohini De A. Seneviratne; K. C. S. Dalpathadu (College of Community Physicians of Sri Lanka, 1997)
Objective: To develop Modules on Distance Education (DE) for Public Health Midwives (PHMM) on the postpartum care of the mother and the care of the newborn.   Methodology: In the preparation of the distance education modules a comprehensive needs assessment was carried out in order to identify the training needs of PHMM.   A nominal group discussion was carried out to determine the most important and appropriate study topics for the programme. A partial participatory method was used to develop the curriculum. The distance education modules were prepared by a team of authors adhering to the standards and the principles of distance writing. The modules were pre-tested on PHMM and appropriate changes were made.   Results and Conclusions: Two modules were developed on, "Postpartum care of the mother" and "Care of the newborn". The methodology adopted' was found to be effective in the development of the modules.